INOVASI KLAMPID DALAM PENINGKATAN PELAYANAN ADMINISTRASI KEPENDUDUKAN PEMBUATAN AKTA KELAHIRAN DI KELURAHAN BARATAJAYA KOTA SURABAYA - Thenu, Anastasya Priskila Priskila Elisabeth Thenu; Bambang Kusbandrijo; Anggraeny Puspaningtyas (Madika: Jurnal Politik dan Governance, 2023)
Public service innovation is said to be a breakthrough initiative from public agencies/institutions in an effort to improve the quality of public services. One of the new breakthroughs to improve the quality of public services provided by the Surabaya City Population and Civil Registry Office is the Klampid program in population administration services, especially the making of birth certificates. This study aims to analyze the success of Klampid’s innovation in improving population administration services for making birth certificates in the Baratajaya Village, Surabaya City. The type of research used is descriptive qualitative method. While the research focus uses E-Government theory according to Harvard JFK School which has 3 elements, namely Support, Value, and Capacity. The results of this study indicate that the implementation of Klampid in making birth certificates has been going well, and is optimal because the community can benefit from having this Klampid providing services that are easy, fast, and do not require any costs. However, there are still things that need to be improved, such as more socialization for the community to understand and understand the programs implemented by the government and facilities and infrastructure such as computers, printers and scanners need to be improved.